(untitled) (Pulse, 2016)
A 56 years old diabetic hypertensive male was admitted through neurosurgery OPD with the complaint of vision problems in the right eye for the last 1 and 1/2 years. Peri-metry reveals bilateral temporal field defects and MRI examination showed a sellar and suprasellar mass infiltrating the surrounding structures including cavernous sinus. Histomorphologically and inmmunohistochemically, a diagnosis of atypical pituitary adenoma was made. Pulse Vol.8 January-December 2015 p.66-68